2021
DOI: 10.1042/bsr20203282
|View full text |Cite
|
Sign up to set email alerts
|

The role of phosphoprotein phosphatases catalytic subunit genes in pancreatic cancer

Abstract: Compelling evidence suggests that phosphoprotein phosphatases (PPPs) are involved in a large spectrum of physiological and pathological processes, but little is known about their roles in pancreatic cancer. We investigated the expression level, prognostic value, and potential function of PPPs with data from Oncomine, GEPIA, THPA, and TCGA databases and an independent cohort of patients with pancreatic cancer. Among all the PPP catalytic subunits (PPPcs), the transcription levels of PPP1CA, PPP1CB, PPP3CA, PPP3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
(50 reference statements)
3
7
0
Order By: Relevance
“…Finally, while the molecular function of phosphatase encoded by PPEF1 is not known in detail, it has been connected to apoptosis regulation and the response to calcium (Ca 2+ is also second messenger controlling cell death) 64 . It exerts a tumorigenic role in breast cancer 65 and was found to be overexpressed in pancreatic carcinoma 66 which confirms both its prognostic value in LUAD (poorer survival when highly expressed) and literature data regarding lung cancer 64 .…”
Section: Discussionsupporting
confidence: 77%
“…Finally, while the molecular function of phosphatase encoded by PPEF1 is not known in detail, it has been connected to apoptosis regulation and the response to calcium (Ca 2+ is also second messenger controlling cell death) 64 . It exerts a tumorigenic role in breast cancer 65 and was found to be overexpressed in pancreatic carcinoma 66 which confirms both its prognostic value in LUAD (poorer survival when highly expressed) and literature data regarding lung cancer 64 .…”
Section: Discussionsupporting
confidence: 77%
“…The PPP2CA gene encodes the α subtype of the PP2A catalytic subunit, which regulates PP2A activity by selecting PP2A regulatory subunits (12). In previous studies, the upregulation of PPP2CA was considered to be related to the poor prognosis of triple-negative breast cancer (13) and pancreatic cancer (14). High expression of PPP2CA is also related to glioma, and mir-130b-ceRNA can promote the epithelial-mesenchymal transition and invasion of glioma by targeting PPP2CA (15).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support the hypothesis that PPP1CB facilitates the progression of PAAD. The expression of PPP1CB [16] .…”
Section: Discussionmentioning
confidence: 99%
“…These data demonstrate that the expression levels of PPP1CB in PAAD tissue may have prognostic significance in predicting outcomes for patients with PAAD. In recent years, it has been reported that PPP1CA, PPP1CB, PPP2CA, PPP2CB , and PPP3CA accelerate the progression of pancreatic cancer, while PPP3CB, PPP5C , and PPP6C hinder PAAD progression [ 16 ] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation